Competition in Alpine ski-racing - P.J. Gómez (Asociación Española de Ciencias del Deporte, 2010)
This articles aims at analysing the present situation of alpine ski-racing, making a careful study of certain essential aspects, why it is initiated, how the training is carried out, what should be known about racing, etc. At the same time, it is intended to be the first of series of reflections about alpine ski-racing. Others studies will talk about aspects more connected to the development and for training, the characteristics, aims and principles of competitive skiing in the various disciplines, the specific methodology of work in each, etc. In this work, we try to deal whit the bases, demands and initial conditioning to establish a process of long-term competitive ski training of elite racers, we also discuss a series of factors which must be borne in mind when organising training, when to start racing training. The study finishes with some conclusions about alpine ski-racing. KEY WORDS: Alpine ski-racing, trainement start